EVALUASI SISTEM DISPOSISI SURAT DALAM ADMINISTRASI RUMAH SAKIT - Arma Anugrah Febriani; Muhammad Aditya Rachman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2026)
The mail disposition system is a crucial component in hospital administration, serving as a mechanism to ensure effective information flow, coordination, and decision-making processes. This study aims to evaluate the effectiveness of the mail disposition system in hospital administration based on recent scientific literature. The research method employed is a descriptive qualitative approach through a literature review. The findings indicate that the implementation of an electronic disposition system significantly improves efficiency, accuracy, and transparency in administrative processes. However, several challenges persist, including limited technological infrastructure, inadequate human resource competencies, and resistance to digital transformation. Therefore, the integration of a comprehensive electronic disposition system is recommended to enhance hospital administrative performance and service quality.